Indirect vector control for induction motor drive using two level and five level inverter - Ankit Agrawal; Rakesh Singh Lodhi; Pragya Nema (International Journal of Applied Power Engineering (IJAPE), 2019)
This paper represent modelling & simulation of indirect vector control for induction motor drive using two level and five level inverter. To overcome of lower order harmonics, THD & speed torque characteristics of three phase squirrel cage induction motor. This paper provides solution through indirect vector control & SPWM technique for multilevel inverter. A comparison and performance of two level and five level inverter are used in motor to control speed, current and torque. Matlab simulation environment are taken to simulate indirect vector control for induction motor drive using two level and five level inverter, so torque ripple minimization, lower order harmonics are reduced, constant speed, constant torque and variable speed variable torque are determined through simulation results. The applications under operating conditions are performed better THD, better reliability in AC drives.